The Patterns of Sports Coaching on Athletic Achievement PASI - I Gusti Ngurah Putra Wira Prasetya; Suratmin Suratmin; Syarif Hidayat (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
The pattern of sports coaching is a step in improving sports performance. This study aimed to analyze the pattern of sports coaching on athletic achievement at PASI Buleleng, Bali. The research method used descriptive qualitative. The research sample was 43 people. Data were collected through observation and surveys, questionnaires, interviews, and archives. Data analysis with the triangulation technique is a method to test the validity of the data. The conclusions of the study indicate that the pattern of sports coaching on athletic sports achievement (1) the pattern in promoting athletic achievement at Indonesian Athletic Association (PASI) Buleleng applied an athlete recruitment system with a natural and direct approach by the coach, (2) the training program in athletics is still conducted in general for the number of competitions and did not implement mental training, (3) the Indonesian Athletic Association (PASI) in Buleleng is under the PASI of Bali Province, (4) the facilities and infrastructures are managed by Indonesian National Sports Committee (KONI) Buleleng, and (5) the funding system comes from the Buleleng KONI budget. Based on the conclusions, it is suggested that the sports coaching system for athletic achievement needs to be improved on the athlete recruitment system, coaching management, mental training program, and funding as needed, and it is important to evaluate coaching so that athletic sports achievement at Indonesian Athletic Association (PASI) Buleleng Bali is achieved optimally.